If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10(2x-9)=4(x-8)-22
We move all terms to the left:
-10(2x-9)-(4(x-8)-22)=0
We multiply parentheses
-20x-(4(x-8)-22)+90=0
We calculate terms in parentheses: -(4(x-8)-22), so:We get rid of parentheses
4(x-8)-22
We multiply parentheses
4x-32-22
We add all the numbers together, and all the variables
4x-54
Back to the equation:
-(4x-54)
-20x-4x+54+90=0
We add all the numbers together, and all the variables
-24x+144=0
We move all terms containing x to the left, all other terms to the right
-24x=-144
x=-144/-24
x=+6
| x+1/2+x+2/3=2x-5/7+9 | | 20y=16 | | -0.7x+0.8x=0.05 | | p=2p-31 | | 19r=15 | | 9w+4/2+5w+4/3=48 | | -6h^2-10=590 | | (5-u)(4u+9)=0 | | 2.1/4r=10 | | 8a-8=16+2a | | z+70=2(z+20) | | t+942=1792 | | -2(x+5)+4=7x+14-3x | | 6b^2+3b-18=0 | | 4=-2x+9 | | 3(4x+4)-7x=-23-2x | | x-69=14 | | 3x*4x=147 | | 10+(2-x)=7 | | 3q+8=32 | | (3.5)2t+1=525.21875 | | 66=6k+6 | | 5-x/14=13/28 | | x+2x-5+71+123=360 | | 88=6m+58 | | 297=33c+99 | | 15/12x-25=0 | | 3x+-15=2x+10 | | x+2x-5+71+123=180 | | f(7)=2*7-3 | | -v/5=9.8 | | 3D+5=d-23 |